Odpowiedzi

2009-11-12T15:30:37+01:00
X/2- x/3+ x/4- x/6+ x/12 -1 = -2/3
Lewa strona r-nia
L:x/2-x/3+x/4-x/6+x/12-1= (6x-4x+3x-2x+x-12)/12=(4x-12)/12= x-3/3 zatem sprzeczność
1 1 1
Najlepsza Odpowiedź!
2009-11-12T15:31:37+01:00
X/2 - x/3 + x/4 - x/6 + x/12 - 1 = - 2/3 /:12 (calosc przez 12)
6x - 4x + 3x - 2x + x -12 = -8
6x - 4x + 3x - 2x + x = 12 - 8
6x - 4x + 3x - 2x + x = 4
4x = 4 /:4 (calosc przez 4)
x = 1
1 5 1
2009-11-12T15:45:09+01:00
X/2- x/3+ x/4- x/6+ x/12 -1 = -2/3 /÷12
6x-4x+3x-2x+x-12=-8
6x-4x+3x-2x+x=12-8
4x=4 / ÷4
x=1